Alkylarylation of N-allylbenzamides and N-allylanilines with simple ethers for the direct construction of ether substituted dihydroisoquinolinones and indolines. Issue 4 (10th January 2020) - Li, Yiting; Sun, Song; Cheng, Jiang; Yu, Jin-Tao
Abstract : A radical-initiated alkylarylation of unactivated alkenes with ethers to form ether-substituted dihydroisoquinolinones and indolines was achieved. Abstract : A radical-initiated cascade addition and cyclization of N -allylbenzamides with simple ethers to construct ether-substituted dihydroisoquinolinones was performed in the presence of CuI. The cleavage of the sp 3 C–H bond in ether and the sp 2 C–H bond in phenyl was involved in this reaction. Moreover, the arylalkylation of N -allylanilines was also realized under similar reaction conditions, providing ether-functionalized indolines in good to moderate yields.